1977
DOI: 10.1016/0304-3959(77)90034-3
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of morphine and stimulus-produced analgesia by subtotal spinal cord lesions

Abstract: This study examined the hypothesis that descending inhibitory pathways from brain stem to spinal cord mediate the analgesic effect of both electrical brain stimulation and morphine. In the first set of experiments, the effect of subtotal midthoracic spinal cord lesions on the analgesic effect of electrical stimulation in the periaqueductal gray matter of the rat was examined. In the second, the effect of similar cord lesions on the analgesic effect of intraperitoneal morphine was studied. In both cases, a lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 298 publications
(69 citation statements)
references
References 27 publications
5
63
0
1
Order By: Relevance
“…It is of interest that the earliest studies of stimulation-produced analgesia pointed to the midline dorsal raphe, rather than the PAG as the critical target for generating analgesia (Mayer et al, 1971;Akil and Mayer, 1972;Guilbaud et al, 1973;Liebeskind et al, 1973;Basbaum et al, 1977). In fact, because putative serotonin antagonists blocked the analgesia and inhibition of the firing of spinal cord "pain" responsive neurons, the Besson group concluded that the 5HT neurons of the DR were key to initiating the descending controls (Guilbaud et al, 1973;Liebeskind et al, 1973).…”
Section: Output Of the Midbrain Serotonergic Neuronsmentioning
confidence: 99%
“…It is of interest that the earliest studies of stimulation-produced analgesia pointed to the midline dorsal raphe, rather than the PAG as the critical target for generating analgesia (Mayer et al, 1971;Akil and Mayer, 1972;Guilbaud et al, 1973;Liebeskind et al, 1973;Basbaum et al, 1977). In fact, because putative serotonin antagonists blocked the analgesia and inhibition of the firing of spinal cord "pain" responsive neurons, the Besson group concluded that the 5HT neurons of the DR were key to initiating the descending controls (Guilbaud et al, 1973;Liebeskind et al, 1973).…”
Section: Output Of the Midbrain Serotonergic Neuronsmentioning
confidence: 99%
“…It is well established that electrical stimulation of portions of the medial brainstem can inhibit both vocalization to nociceptive stimuli and spinally mediated nociceptive reflexes (Reynolds 1969;Mayer et al 1971;Oliveras et al 1974;Akil and Liebeskind 1975;Basbaum et al 1977;Basbaum and Fields 1979). The inhibitory signal, is believed to originate in the periaqueductal gray, travel to the rostroventral medulla, including the nucleus raphe magnus (NRM), and then to the spinal cord through serotonergic fibers that descend through the DLF to suppress firing of neurons within the dorsal horns (Mayer et al 1971;Oliveras et al 1974;Fields 1979, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…For example, systemic morphine was less effective in increasing the threshold in the tail flick test (which is generally accepted as a spinal reflex) in spinally transected as compared with intact rats (Advokat & Burton, 1987;Sinclair et al, 1988). Lesions of the dorsolateral funiculus or of brainstem nuclei reduced the effectiveness of systemic morphine in this test (Murfin et al, 1976;Basbaum et al, 1977;Yaksh & Rudy, 1977;Hayes et al, 1978;Barton et al, 1980).…”
Section: Introductionmentioning
confidence: 99%